An Analysis of the Health Indonesia Program with a Family Approach at the Local Government Clinic in the City of Tidore Islands North Maluku, Indonesia - Dewi Indra Purwanti; Grace Korompis; Windy Wariki; Idris Sudin (International Journal of Education, Information Technology, and Others, 2021)
The objective of this study was to determine the implementation of the Indonesia Healthy Program with a Family Approach (PIS-PK) in Local government Clinic at Tidore Islands. This research is qualitative research, its take place in 2 Local government clinic namely, Soasio Local Government Clinic and TomalouLocal Government Clinic. Those two Local governmentclinics are location in Tidore City, North Maluku Province, carried out from April to August 2019. The results of the study concluded that in general, the implementation of PIS-PK at the level of Local government clinic in the City of Tidore Islands has been implemented as well as the program implementation guidelines. In the event that the socialization process has been carried out according to the objectives and stages in the program activity plan, it is necessary to increase cross-sectorial synergy and elements of interest. Availability of Human Resources in public health canters has been in accordance with the needs of program implementation, but it is necessary to evaluate performance and increase competence to improve the services. The activity budget is available from the Health Operational Assistance (BOK) as well as the National Health Insurance (JKN) capitation and routine funds for Local Government Clinic, but a budget allocation for additional medical tools is required for follow-up interventions for society conditions and service needs at Local Government Clinic . Family Health Profile (PROKESGA) data is available, but needs to continuous updating. The Family Information Package (PINKESGA) as a family education instrument is also available. PIS-PK activities running well because of a roadmap with an activity plan, which is agreed with the relevant elements as a reference for the implementation of PIS-PK activities. The suggestions from this research consist of: (1) socialization of the program to the society must be improved: (2) the health department needs to conduct an evaluation; and (1) the society must cooperate in helping Local Government Clinic improve the family health index.